Here's the question you clicked on:
Gretchen2013
Given: x – (5 – 3x + 2) = 15 + 3x Prove: x = 22 attatchment below OPTIONS What are the missing justification steps, in order? Commutative Property of Addition, Combine Like Terms, Distributive Property Associative Property of Addition, Distributive Property, Multiplication Property of Equality Associative Property of Addition, Commutative Property of Addition, Distributive Property Associative Property of Addition, Distributive Property, Addition Property of Equality
No it is easy if you know all the properties...
plug the value of x in the equation to prove it
22-(5-3(22)+2)=15+3(22)
Just wait @jiteshmeghwal9
You have to find x.. Just suppose that 22 is not the answer for 10 minutes.. @Gretchen2013
x – (5 – 3x + 2) = 15 + 3x <-- VERY SIMPLE equation. First we want to do distributive property. We want to distribute the negative sign to the (5-3x+2) So then the equation will become.. x-5+3x-2=15+3x Now that we have our new equation -> x-5+3x-2=15+3x Lets break it down a bit more, By combining like terms! We will combine our x's together. so.. x-5+3x-2=15+3x will become.. 4x-5-2=15+3x Now, that we have combined our x's on one side, let us also combine the simple numbers together. So.. 4x-5-2=15+3x will become.. 4x-7=15+3x Now that we have our new equation -> 4x-7=15+3x This will become very easy to solve! 4x-7=15+3x We can start by adding the 7 to both sides. 4x-7=15+3x +7 +7 ------------ 4x=22+3x now we will subtract 3x on both sides. 4x=22+3x -3x -3x ---------- x=22
theanks for explaining! @karatechopper
Most welcome! @Gretchen2013
Hey i used Option D on here.